Multidimensional Radar Waveforms: A New Paradigm for the Design and Operation of Highly Performant Spaceborne Synthetic Aperture Radar Systems - Krieger, Gerhard; Gebert, Nicolas; Moreira, Alberto (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2007)
This paper introduces and analyses the innovative paradigm of multidimensional waveform encoding for spaceborne synthetic aperture radar (SAR). The combination of this technique with digital beamforming on receive enables a new class of highly performant SAR systems employing novel and highly flexible radar imaging modes. Examples are adaptive high-resolution wide-swath SAR imaging with compact antennas, enhanced parameter estimation sensitivity for applications like along-track interferometry and moving object indication, and the implementation of hybrid SAR imaging modes that are well suited to satisfy the hitherto incompatible user requirements for frequent monitoring and detailed mapping. Implementation specific issues will be discussed and examples demonstrate the potential of the new technique for different remote sensing applications. © 2007 IEEE.
DLR Import::2019-04-03